A Facile Preparation Method of ZrO2 Hollow Sphere Using PVA Microcapsule as a Template - Lee Dong-Hee; Lee Seon-Geun; Ryu Jae-Chun; Kim Young-Ho (MATEC Web of Conferences, 2016)
In this study, we proposed a simple and facile preparation method of ZrO2 hollow sphere using PVA microcapsule as a template. The prepared hollow sphere was characterized by XRD, FESEM, N2 adsorption/desorption isotherms, FT-IR techniques. PVA microcapsule were prepared by polymerization in a water-in-oil emulsion and coated by adding of zirconia sol. Uniform and spherical shaped zirconia hollow sphere with very narrow size distribution was obtained after calcination at 700 °C by removing the PVA microcapsule template. No other carbon residues and carbon-zirconium compounds were observed. These results indicate that the zirconia capsule formed without deformation of the zirconia shell structure, and CO2 and H2O gases by decomposition of the PVA microcapsule during sintering process removed through the zirconia shell.